Influence and Application of Texture in the Works of Contemporary Iranian Painters (From 1987 to 2017) - Torkzadeh, Ebrahim; Afshari, Morteza (Journal of History Culture and Art Research, 2019)
Visual elements are one of the most prominent dimensions of visual arts which through it the broadest and most widely concepts are perceived by various human communities composed of different races and nationalities. Texture is very important as one of the visual elements influencing the artwork, especially painting works due to its visual appearance. Contemporary Iranian painters, like other painters in the world, have used the element of texture and created countless artworks. The authors examine the works of 10 contemporary Iranian painters in this regard. Accordingly, in this research, it is attempted to study the works of these artists by analytical-descriptive method with the aim of influencing the visual element of the texture as well as effectiveness on conveying the expression and meaning to the audience. The results of library and field studies show that the painters used different types of visual elements of textures in their works: actual texture, simulated texture, abstract texture and invented texture. Each of these artists has drawn design with regard to their social, emotional, and intellectual concerns of different types of textures to express their subject matter to the audience better. In fact, these painters have been able to create a remarkable and diverse work in terms of composition and visual features from the texture.